Technology-based archives management: How much does it matter to organizations? - Fitriani, Somariah; Muljono, Hery; Fetrimen, Fetrimen (Community Empowerment Journal, 2024)
Technology-based record management, which is part of the development of information and communication technology (ICT) plays an important role for organizations in managing documents to be more effective and efficient. Thus, such training needs to be carried out, one of which is through community service activities. The purpose of this training was to educate participants to understand the importance of this training topic and be able to practice it directly as part of a technology literate society. This training was conducted by the community service team consisting of three lecturers and two students The training was carried out virtually through the Zoom platform for four hours, which the community service partner was PCM Bekasi Timur. The stages are divided into four parts, 1) the delivery of core material and best practices; 2) a question-and-answer session; 3) the conclusion and summary of the material; and 4) the impressions and messages conveyed by representatives of the participants. The evaluation results showed that 6 (54.5%) participants were satisfied and 4 (36.4%) participants were very satisfied, and 1 (9.1%) participant was not satisfied with the activities. In addition, they mostly showed their satisfaction and enthusiasm with the presented material and the delivery of spokespersons, which can also be seen from the positive impression of the participants. It is inferred that this training provides great benefits for participants and organizations to improve their archival documentation system.